2013
DOI: 10.1017/s0021932013000163
|View full text |Cite
|
Sign up to set email alerts
|

Household Roles and Care-Seeking Behaviours in Response to Severe Childhood Illness in Mali

Abstract: Malaria is a major cause of under-five mortality in Mali and many other developing countries. Malaria control programmes rely on households to identify sick children and either care for them in the home or seek treatment at a health facility in the case of severe illness. This study examines the involvement of mothers and other household members in identifying and treating severely ill children through case studies of 25 rural Malian households. A wide range of intra-household responses to severe illness were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
4
38
1
Order By: Relevance
“…These include insufficient supply of high quality health commodities and trained health workers, poor geographic access to services, poor quality of care, as well as user-related financial and non-financial barriers [2]. As has been well documented, in sub-Saharan Africa these user-related barriers are locally specific, and can include cultural beliefs; perceptions of illness; illness severity and efficacy of treatment; social norms around household decision-making and gender; location; household income and direct and in-direct costs of treatment; and perceptions of and previous experiences with health services [3], [4], [5], [6]. In many countries, these supply- and demand-related barriers have had a significant impact on progress towards the achievement of Millennium Development Goal (MDG) 4 [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…These include insufficient supply of high quality health commodities and trained health workers, poor geographic access to services, poor quality of care, as well as user-related financial and non-financial barriers [2]. As has been well documented, in sub-Saharan Africa these user-related barriers are locally specific, and can include cultural beliefs; perceptions of illness; illness severity and efficacy of treatment; social norms around household decision-making and gender; location; household income and direct and in-direct costs of treatment; and perceptions of and previous experiences with health services [3], [4], [5], [6]. In many countries, these supply- and demand-related barriers have had a significant impact on progress towards the achievement of Millennium Development Goal (MDG) 4 [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…This role has been well documented in countries with a high rate of mortality due to HIV/AIDS, but it is also important elsewhere, in other contexts. A study carried out in 2006-2007 in rural Mali has shown that the oldest women present in the household play an active role when children fall ill (Ellis 2013); the same has been shown for rural Ethiopia (Gibson and Mace 2005). Hence it is important to identify such ties in children's family environment.…”
Section: Classification Of Kinship Tiesmentioning
confidence: 99%
“…Another trait of families in Africa is that parental roles may be delegated to different relatives, notably via the tradition of child fostering (Goody 1978;Isiugo-Abanishe 1994). Parents are not the only relatives who raise children, especially concerning health (Adams, Madhavan, and Simon 2002;Ellis et al 2013). The extended family network is called upon to play a central role, and its members have obligations to children.…”
Section: Introductionmentioning
confidence: 99%
“…Many frameworks inadvertently impose etic categories of well-being on households from externally derived frameworks (Adams et al 1998). Furthermore, these categories are not set in stone and need to be continuously confi rmed, as they can change over time and with changing sociohistorical, political and economic conditions; they also may not be the same across all members of a household (Ellis et al 2013). While there has been a signifi cant body of research examining gendered roles and responsibilities, the social reproduction of gender roles within the household, and the eff ects of diff erent household structures on women's and men's health and well-being, less has been done to understand the diff erent goals and objectives of individuals within a single household and to what extent these are gendered, for example.…”
Section: Challenges Within the Current Literaturementioning
confidence: 99%